Underlying Structure of Online Risks and Harm among Bangladeshi Teenagers - Taher, Taslim; Suhaimi, Mohd Adam; Molok, Nurul Nuha Abdul (Applied Information System and Management (AISM), 2020)
This paper gives an account of the consequences of the procedure of EFA (exploratory factor analysis) invoking online risks as well as harm information acquired by an overview of 443 adolescents in Bangladesh. The information was gathered utilizing a 42-item, adjusted Likert survey investigating the critical variables. PCA (Principal Component Analysis) with Varimax rotation was chosen by the researcher to accomplish it. Based on data, the procedure took out the crucial factors social, religiosity, psychological, online risks as well as harm. 65.594% of the variance was clarified by these nine dimensions together. The procedure of reliability analysis generated internal consistency estimates which may be considered acceptable. The range was found from 0.625 which belongs to Emotional Problems to 0.930 which belongs to Online Risks. These discoveries give comprehensive justification to build the legitimacy for the items. The presence of the components influencing altogether the young people online in Bangladesh has been identified as well.